2004
DOI: 10.1074/jbc.m407329200
|View full text |Cite
|
Sign up to set email alerts
|

Use of Molecular Simulation for Mapping Conformational CYP2E1 Epitopes

Abstract: The identification of the epitopes recognized by autoantibodies against cytochrome P450s (CYPs) associated with drug-induced hepatotoxicity is difficult because of their conformational nature. In the present investigation, we used a novel approach based on the analysis of the whole molecule antigenic capacity following single amino acid substitutions to identify the conformational epitopes on CYP2E1. A molecular model of CYP2E1 was generated based on the CYP2C5 crystal structure, and potential motifs for amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 28 publications
3
21
0
2
Order By: Relevance
“…In this context, it has been observed that about 40% of patients with advanced ALD have circulating IgG directed against CYP2E1 (Vidali et al 2003). These autoantibodies recognize at least two distinct conformational epitopes present in the C-terminal portion of the CYP2E1 molecule (Vidali et al 2004). One of the mechanisms proposed to explain the formation of anti-CYP autoantibodies postulates that the binding of reactive drug metabolites to CYP promotes a humoral immune response against the modified protein and concomitantly favours the activation of normally-quiescent auto-reactive lymphocytes, which leads to the production of antibodies to the native CYP molecules (Van Pelt et al 1995).…”
Section: Free Radical Mechanisms In Immune Reactions Associated With mentioning
confidence: 99%
“…In this context, it has been observed that about 40% of patients with advanced ALD have circulating IgG directed against CYP2E1 (Vidali et al 2003). These autoantibodies recognize at least two distinct conformational epitopes present in the C-terminal portion of the CYP2E1 molecule (Vidali et al 2004). One of the mechanisms proposed to explain the formation of anti-CYP autoantibodies postulates that the binding of reactive drug metabolites to CYP promotes a humoral immune response against the modified protein and concomitantly favours the activation of normally-quiescent auto-reactive lymphocytes, which leads to the production of antibodies to the native CYP molecules (Van Pelt et al 1995).…”
Section: Free Radical Mechanisms In Immune Reactions Associated With mentioning
confidence: 99%
“…The correct sequence of the inserts was confirmed by automated DNA sequencing. Wild-type and mutated CYP2E1 variants were expressed and purified as previously reported [22].…”
Section: Site-directed Mutagenesis Of Cyp2e1 and Prokaryote Expressiomentioning
confidence: 99%
“…Anti-CYP2E1 auto-antibodies from ALD patients are similar to those associated with halothane hepatitis and recognize at least two distinct conformational epitopes in the C-terminal portion of the molecule [78]. These epitopes are located in the molecule surface and account for the recognition by anti-CYP2E1 IgG of CYP2E1 expressed on the outer layer of the hepatocyte plasma membranes [78].…”
Section: Possible Mechanisms In the Development Of Immune Responses Imentioning
confidence: 99%